2012
DOI: 10.1186/1742-2094-9-137
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation in the injured central nervous system: another dual-edged sword?

Abstract: The complement system, a major component of the innate immune system, is becoming increasingly recognised as a key participant in physiology and disease. The awareness that immunological mediators support various aspects of both normal central nervous system (CNS) function and pathology has led to a renaissance of complement research in neuroscience. Various studies have revealed particularly novel findings on the wide-ranging involvement of complement in neural development, synapse elimination and maturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 148 publications
2
99
0
Order By: Relevance
“…These studies indicated that the acute phase of inflammation might exacerbate the secondary injury after SCI, while the chronic phase could have a protective effect. Even C5a could probably have an opposite role during this second phase, as Beck et al [30] predicted that the blocking of subacute to chronic inflammation by the C5a receptor antagonist would reduce functional recovery after SCI, which was confirmed in CD88 −/− mice by Brennan et al [9]. Perhaps for this reason, in our study the functional recovery of control mice started from 15 days after injury.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These studies indicated that the acute phase of inflammation might exacerbate the secondary injury after SCI, while the chronic phase could have a protective effect. Even C5a could probably have an opposite role during this second phase, as Beck et al [30] predicted that the blocking of subacute to chronic inflammation by the C5a receptor antagonist would reduce functional recovery after SCI, which was confirmed in CD88 −/− mice by Brennan et al [9]. Perhaps for this reason, in our study the functional recovery of control mice started from 15 days after injury.…”
Section: Discussionsupporting
confidence: 69%
“…However, it was reported recently that complement activation had another neuroprotective role [6][7][8][9] in addition to that involving the secondary injury [10,11], and C5a was thought to be the most important factor in this respect. Although C5a can induce the chemotactic response and mediate the early phase of inflammation that is harmful to cells at the lesion site [12,13], it can exert its neuroprotective effect by inhibiting neurone apoptosis [6,7,14] and promoting microglial phagocytosis [15,16], which is beneficial in alleviating the secondary injury.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, C3a protects neurons against N-methyl-D-aspartate (NMDA)-induced excitotoxicity in a dose-and astrocyte-dependent manner (Van Beek et al, 2001), while C5a exposure causes upregulation of nerve growth factor (NGF) in astrocytes, with similar neuroprotective effects in vitro (Jauneau et al, 2006). The role of the complement after ischemic stroke in vivo is yet to be fully elucidated, and the complexity of experimental animal studies suggests that complement activation could be a "dual edged sword" exerting beneficial or detrimental effects depending on its timing and context (Brennan et al, 2012).…”
Section: Neuronal Functional Plasticitymentioning
confidence: 99%
“…A number of animal and human studies [29][30][31][32][33][34][35][36][37][38][39] , including our own [40][41][42] , demonstrated that activation of the complement system play a decisive role in the pathophysiology of IS. No study has reported data on functional state of FH and FL in this disorder.…”
Section: Discussionmentioning
confidence: 99%